METHODS OF INTERACTIVE TRAINING IN ADVANCED TRAINING OF INFORMATION AND ANALYTICAL LAW ENFORCEMENT AGENCIES OF UKRAINE - Артюшин, Г. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article is devoted to justification of methods of interactive training in advanced training of information and analytical departments of law enforcement agencies of Ukraine. The critical analysis on present theoretical statements on interactive training is given. The analysis of researches suggesting the use of interactive teaching methods in military education is done. The importance of interactive teaching methods in advanced training of information and analytical departments of law enforcement agencies of Ukraine is proved. The methods used in the preparation of such interactive methods of teaching are as following: discussion, role playing and interactive demonstrations. It is proved that the workshops based on interactive teaching methods increase the efficiency of advanced training in information and analytical departments of law enforcement agencies of Ukraine